CHARACTERISTIC FEATURES OF SECURITIES DEVELOPMENT IN THE MIDDLE EAST - Almarashdi А. (SWorldJournal, 2020)
. The stages of development of the securities market of the Middle East are analyzed. The countries listed in the article traditionally represent countries whose economies exist in accordance with the requirements of the Islamic model. Religion as a world